Acoustic energy: a new transfection method for cancer of the prostate, cancer of the bladder and benign kidney cells - Michel, Maurice Stephan; Erben, Philipp; Trojan, Lutz; Schaaf, Axel; Kiknavelidze, Koba; Knoll, Thomas; Alken, Peter (Anticancer research, 2004)
Background: Clinical use of gene therapy is limited by the poor efficacy and accuracy of intracellular DNA delivery. Known concepts of DNA transfection have not yet become clinical routine in the treatment of human disorders. We therefore focused on new transfection methods using different forms of acoustic energy as potentially safe and topographically applicable methods for gene delivery in the field of urology. Materials and Methods: Three different cell lines (prostatic and urothelial cancer, benign kidney) were transfected by different forms of acoustic energy. The effect of several parameters of electromagnetic shock wave treatment (number and frequency of impulses, energy flow density and plasmid concentration) as well as focused ultrasound on the transfection rate was assessed in a standardized experimental setup. The transfection rate was measured through reporter genes (pEGFP) by FACScan. Transfection by lipofectamine and electroporation served as positive controls. Results: All cell lines were transfectable by acoustic energy. Maximum transfection rate was achieved using focused ultrasound (49.5%; 200 W, 500 ms, 200 μg/ml DNA). 31.3% of kidney cells were transfected by electromagnetic shock waves (1500 impulses, 200 μg/ml DNA, 0.5 mJ/mm2 energy density, 2 Hz). Plasmid strand breaks were identified as a limiting factor of the transfection rate. Conclusion: Transfection by acoustic energy, especially focused ultrasound, can be achieved at a high level in different cell lines. The possible topical application to urological organs and the low level of side-effects make acoustic energy a promising new gene therapy treatment option in urology.
Gesehen am 07.03.2022